Prussian blue analogs cathodes for aqueous zinc ion batteries. (October 2022) - Li, Yuanxia; Zhao, Jingxin; Hu, Qiang; Hao, Tianwei; Cao, Heng; Huang, Xiaomin; Liu, Yu; Zhang, Yanyan; Lin, Dunmin; Tang, Yuxin; Cai, Yongqing
Abstract: Aqueous zinc ion batteries (AZIBs) with high theoretical capacity, low cost, and highly safety that have been considered as one of the most promising candidates for the next generation of electrochemical energy storage applications. However, the hydrated zinc ions have strong electrostatic force with the host material, causing the low output voltage and poor reversibility. Thus, exploiting suitable cathode materials with high voltage, specific capacity, and stable cycling performance is still a challenge. Recently, the development of cathode materials mainly focuses on manganese-based, vanadium-based, organic, and Prussian blue analog (PBAs) materials. Among these cathodes' materials, PBAs have attracted great attention for AZIBs owing to their high working voltage, tunable chemical composition and microstructure, open 3D frameworks, low cost, and ease of synthesis. To record the recent rapid development PBAs materials toward high-performance AZIBs, we provide fundamental insights into the structure characteristics and synthesis control of PBAs and present an overview of recent developments of PBAs as promising cathodes for AZIBs. Finally, the key challenges and future opportunities in this rapidly developing field are also presented in this review. Graphical abstract: Image 1 Highlights: The structural features of PBAs are introduced. The development status of PBAs as cathodes for AZIBs is summarized. Regulation strategies and outlook for PBAs cathodes as AZIBs are discussed.